THE INTRINSIC ELEMENTS OF REMBULAN TENGGELAM di WAJAHMU - Mahuda Safitri; SIlvi Nuril Maulidia; Rama Garetha Evansam; Aisyah Brilliant; Ahmad Siswanto; Rahmania Firdaus (JOSAR (Journal of Students Academic Research), 2017)
This analysis aims to describe the social values ​​contained in the novel "Rembulan Drowning in Your Face" by Tere-Liye. The approach used in this study is a sociological approach. This sociological approach is a type of literary analysis approach that focuses on the social role contained in the social world. This approach assumes that literary works belong to the community. According to Ratna (2013: 60) a sociological approach, especially for Indonesian literature, both old and modern promises research land that will never dry up. Every work, both on a scale and individual scale, has certain social aspects that can be discussed through social understanding models. The sociological approach also has methodological implications in the form of a fundamental understanding of human life in society. This analysis technique begins by revealing social problems that occur in the world of storytelling novels. The results of the analysis show that the novel "Rembulan Drowned in Your Face" is a novel that illustrates that in life what happens is often not in accordance with what we expect, the opportunity to be able to find answers to five questions obtained by the main character (Ray) shows that often the loss and pain we face in life save so many good things that we often don't realize.